Activity of Δ9-desaturase enzyme in mammary gland of lactating buffaloes - Fernandes, S. A. de Albuquerque; Mattos, W. R.S.; Matarazzo, S. V.; Tonhati, H. [UNESP]; Sundfeld Gama, M. A.; Pazzaneze Duarte Lanna, D. (Taylor & Francis, 2007)
The objective of this research was to measure the activity of Δ9-desaturase enzyme in lactating buffaloes. Data from forty lactating Murrah-crossbred buffaloes were collected on five commercial farms located at Sarapui and Pilar do Sul, Sao Paulo-Brazil. A field survey was done from April to November 2002. In four farms, buffaloes were fed with wet brewers grains (primary concentrate). Only one farm (Farm 4) offered pasture and corn silage. Monthly milk samples were collected and stored at -20°C until analyzed for fatty acid composition. The Δ9-desaturase activity was measured using an indirect method (myristoleic and myristic acids ration - C14:1c9 /C14:0). The higher C14:1c9 /C14:0 rate was verified on Farm 4 (0.092).The C14:1c9 /C14:0 ratio were 0.064 to Farm 1; 0.065 to Farm 2; 0.062 to Farm 3 and 0.065 to Farm 5. The C17:1/C17:0, C18:1c9 /C18:0 and C18:2c9t11/C18:1t11 ratios were also affected. The Farm 4 showed higher value for all ratios. Therefore, in lactating buffaloes grazing pasture the Δ9-desaturase activity could be enhanced.
Keywords: Δ9-desaturase; Fatty acid; Murrah; Pasture